Preaching to Nazi Germany: the pulpit and the confessing church - Skiles, William (Lexington Books/Fortress Academic, 2023)
"In Preaching to Nazi Germany, William Skiles argues that clergy expressed various messages that aimed to limit Nazi interference in church affairs and at times even to undermine the Nazi state and its leaders and policies"--